ATIK LASTİKLERİN İNŞAAT SEKTÖRÜNDE DEĞERLENDİRİLMESİ - Emiroğlu, Mehmet; Yıldız, Servet (My University, 2010)
After fulfillling their useful life the vehicle tires produced with the rubber is becoming a major environmental problem. ıt is necessary many years for self-destruction spontaneously these vehicle tires. so they are cause a major threat in terms of environmental and human health.Reuse the waste vehicle tires became increasingly important environmental problem in consruction sector which is one of the most consumed of the raw materials is very important in terms of environmental protection.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Construction Sektor; Waste tires; Waste management; Conservation of resources